MENGUKUR EFEK PENDIDIKAN KARAKTER TERHADAP REDUKSI PERUNDUNGAN DI SEKOLAH MENENGAH KEJURUAN - Sobirin, Wahyu; Rohendi, Asep; Zajuli, Cecep Mustofa; Wasliman, Eva Dianawati; Wasliman, Iim (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This study evaluates the effectiveness of Character Education Strengthening at SMK Negeri 1 Subang as an effort to shape positive attitudes, behaviors, motivation, and skills in students. In the context of character strengthening as the foundation for the implementation of government regulations, this research focuses on the key role of guidance counselors in three main stages: knowledge, implementation, and habituation. The lack of character education can increase the risk of issues such as rudeness, lack of empathy, and bullying. The research employs a qualitative approach with observation, interviews, and documentation as methods. Results indicate the active participation of the entire school community, the implementation of the P5 program, and regular evaluations. Supportive factors involve the enthusiasm of the school community, understanding of the independent curriculum, and adequate infrastructure, while variations in student backgrounds and challenges in online learning pose obstacles. Positive impacts are evident in the reduction of bullying, a comfortable school environment, and students' improved character. This study provides an in-depth overview of the school's efforts to address bullying through character strengthening, contributing to the creation of a safe and inclusive learning environment.